2004
DOI: 10.1136/bmj.38155.585046.63
|View full text |Cite
|
Sign up to set email alerts
|

Effect of joint crisis plans on use of compulsory treatment in psychiatry: single blind randomised controlled trial

Abstract: Objective To investigate whether a form of advance agreement for people with severe mental illness can reduce the use of inpatient services and compulsory admission or treatment. Design Single blind randomised controlled trial, with randomisation of individual patients. The investigator was blind to allocation. Setting Eight community mental health teams in southern England. Participants 160 people with an operational diagnosis of psychotic illness or non-psychotic bipolar disorder who had experienced a hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
286
4
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(304 citation statements)
references
References 8 publications
3
286
4
11
Order By: Relevance
“…This study additionally found that people with experience of a previous involuntary admission to hospital under the Mental Health Act 1983 had reduced access to social capital, while controlling for the potential confounding effect of diagnosis and length of time known to mental health services. A history of involuntary admission is likely to be a proxy of severity of mental disorder, suggesting that provision of continuous and assertive community-based care to this group, including using interventions such as joint crisis plans (Henderson et al 2004), may be required in order to help them maintain their social networks and enhance their recovery.…”
Section: Discussionmentioning
confidence: 99%
“…This study additionally found that people with experience of a previous involuntary admission to hospital under the Mental Health Act 1983 had reduced access to social capital, while controlling for the potential confounding effect of diagnosis and length of time known to mental health services. A history of involuntary admission is likely to be a proxy of severity of mental disorder, suggesting that provision of continuous and assertive community-based care to this group, including using interventions such as joint crisis plans (Henderson et al 2004), may be required in order to help them maintain their social networks and enhance their recovery.…”
Section: Discussionmentioning
confidence: 99%
“…They have been shown to reduce use of treatment under compulsion and also to reduce costs. (Henderson et al, 2004).…”
Section: What We Heard In Our Evidencementioning
confidence: 99%
“…[292][293][294][295][296] However, there have been very few studies that have explored recovery experiences systematically in BD. Some qualitative studies have explored how individuals with BD stay well, focusing primarily on methods by which relapse is avoided, rather than on the subjective process of recovery, highlighting the importance of both medication and psychosocial support in the context of active condition management by the individual.…”
Section: Cognitive-behavioural Approach To Understanding and Preventimentioning
confidence: 99%